(untitled) (Management Studies and Business Journal (PRODUCTIVITY), 2024)
Mental health in the workplace is increasingly becoming a major concern for organizations, especially in the context of employee resilience and organizational loyalty. This research aims to explore the influence of personalized mental health support strategies on employee resilience and organizational loyalty. Using a systematic literature review approach, this study analyzes relevant literature and finds that tailored support significantly increases employee resilience, which has a positive impact on organizational loyalty. These findings provide important implications for human resource management practices, encouraging organizations to adopt a more personalized approach to mental health support.